2009
DOI: 10.1111/j.1469-0691.2009.02742.x
|View full text |Cite
|
Sign up to set email alerts
|

Commercial potting soils as an alternative infection source of Legionella pneumophila and other Legionella species in Switzerland

Abstract: Legionella spp. are pathogens that can cause Legionnaires' disease in humans through inhalation of contaminated aerosols. The principal reservoir for these microorganisms is water, but Legionella spp. have been isolated from composted vegetable and plant material, and from many potting mixes as well. In Australia, there have been several cases of Legionnaires' disease in which Legionella longbeachae has been isolated from potting soils. In Switzerland, the source of infection cannot always be identified as wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 12 publications
1
66
2
2
Order By: Relevance
“…1) (30)(31)(32)(33). Several species have also been recovered from composts and potting mixes in the United States, Australia, and the United Kingdom and in the soil of Thai farmland (34)(35)(36)(37)(38)(39)(40)(41). At present, there are ϳ56 distinct Legionella species (and many unnamed species) encompassing at least 70 serogroups, approximately half of which have been isolated from, or detected in, clinical specimens, but all species are regarded as potential human pathogens (42,43).…”
Section: Physiology and Ecologymentioning
confidence: 99%
“…1) (30)(31)(32)(33). Several species have also been recovered from composts and potting mixes in the United States, Australia, and the United Kingdom and in the soil of Thai farmland (34)(35)(36)(37)(38)(39)(40)(41). At present, there are ϳ56 distinct Legionella species (and many unnamed species) encompassing at least 70 serogroups, approximately half of which have been isolated from, or detected in, clinical specimens, but all species are regarded as potential human pathogens (42,43).…”
Section: Physiology and Ecologymentioning
confidence: 99%
“…L. longbeachae is the most isolated Legionella sp. from potting soil in Australia (58%), with the rates of isolation of L. pneumophila being 13.3% (10). Against both L. longbeachae and L. bozemanii, the most effective concentration of the citrus EO vapor was 15 mg/liter air.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Currie et al (9) in the United Kingdom has shown that 15 of 24 compost samples were positive for Legionella spp., with L. longbeachae being the most commonly isolated. In one study, L. longbeachae was found in the sputum of a patient who had been in contact with potting soil (6), and it was suggested that aerosolaided spread and evaporation of water in the potting soil were the possible routes of transmission (6,10). Legionella has also been isolated from waste management facilities dealing with unwashed solid articles, probably via exposure to soil (11).…”
mentioning
confidence: 99%
“…A number of studies have investigated the diversity of Legionella species in compost (Steele et al, 1990;Hughes & Steele, 1994;O'Connor et al, 2007;Lindsay et al, 2009;Casati et al, 2009;Pravinkumar et al, 2010) and found a variety of species in high numbers, ranging from 10 3 to 10 5 c.f.u. g 21 .…”
Section: Discussionmentioning
confidence: 99%